Glucagon, cyclic AMP and adrenaline stimulate the degradation of low-density lipoprotein by cultured rat hepatocytes. - Brown, N F (1989)
Rat hepatocytes were preincubated for 16 h with hormones or drugs and then for a further 8 h with 125I-human low-density lipoprotein (LDL). Glucagon (via cyclic AMP) and adrenaline (via cyclic AMP and alpha-effects) increased the binding of 125I-LDL to the LDL receptor, and the degradation of LDL to [125I]iodotyrosine. The effects on degradation were antagonized by dexamethasone, and the action of cyclic AMP on binding and degradation was inhibited by actinomycin D. The results are discussed in relation to the control of lipoprotein metabolism in diabetes.